GEOCHEMICAL INVESTIGATION OF SERPENTINIZED OCEANIC LITHOSPHERIC MANTLE IN THE FEATHER RIVER OPHIOLITE, CALIFORNIA: IMPLICATIONS FOR THE RECYCLING RATE OF WATER BY SUBDUCTION - Li Z.-X.A.; Lee C.-T.A. (My University, 2006)
The petrology and geochemistry of serpentinized harzburgites within the Feather River Ophiolite in northern California were investigated to constrain the origin of serpentinization. Trace-element systematics indicate that serpentinization was associated almost solely with relatively low temperature hydrothermal addition of seawater and not with the addition of metamorphic fluids associated with subduction or tectonic obduction. Major element systematics show almost negligible disturbance, suggesting low water/rock ratios rather than the very high water/rock ratios characteristic of serpentinization of exhumed mantle at the seafloor such as seen in abyssal peridotites. These observations were taken to indicate that serpentinization occurred by the addition of seawater to ultramafic protoliths while they were structurally within the oceanic lithosphere prior to tectonic accretion. Major and trace element systematics were used with simple melting models and assumptions about the thermal state of the mantle to put rough constraints on the paleo-depths at which the ultramafic protoliths were the last melted. Assuming that these peridotites were formed beneath a passive upwelling system, these paleo-melting depths were assumed to equate with paleo-serpentinization depths. For a model mantle potential temperature of 1350 °C, the paleo-serpentinization depth was estimated to be at least ~ 40 km based on the minimum melting degree observed in the Feather River Ophiolite peridotites. This depth constraint on serpentinization was then combined with model estimates of the lateral extent of serpentinization assuming that serpentinization is associated with infiltration of water through faults and fractures. If these observations can be generalized, we estimate that recycling rate of serpentine-bound water in subduction zones is roughly one order of magnitude higher than that associated with mineralogically bound water in subducting oceanic crust and sediments. After accounting for serpentine recycling, it is shown that the recycling rate of water via subduction is roughly equal to the global volcanic dewatering rate, suggesting that the water budget of the ocean and Earth's interior may presently be close to steady state. © 2006 Elsevier B.V. All rights reserved.
Keywords: FEATHER RIVER OPHIOLITE; LITHOSPHERIC MANTLE; SERPENTINIZATION; SUBDUCTION; WATER RECYCLING RATE